Water Erosion in the Moulouya Watershed and its Impact on Dams' Siltation (Eastern Morocco) - A. Sbai (Copernicus Publications, 2021)
The Moulouya watershed presents high risks of water erosion. The dams built on this river lose each year, by siltation, a volume of water of about 10 M m3 (Lahlou, 1994). This worrying rate shows that water erosion can hinder the socio-economic development of the basin if soil protection and siltation measures are not taken. This study defines the areas most threatened by water erosion to protect them as a priority. Using a GIS and the Universal Earth Loss Equation (USLE), we mapped soil losses. The adopted model determines soil loss from erosivity of rainfall, soil erodibility, inclination and slope length, soil cover, and erosion control practices. The possible origins of the deposits alluviating the dams are related to the products of alteration of the Secondary's carbonate formations and the Tertiary and Quaternary formations. The modalities of the transport of deposits of banks of the network of Moulouya are mainly by a suspension. The specific degradation in the Moulouya watershed is estimated at 214 t/km2/year. Precipitation intensity, steep slopes and deforestation are responsible for these losses.